As Contradições do Conceito “cliente é o rei”: da construção social do termo até as práticas organizacionais o caso da Revista HSM Management - Camargo, Maurício Roberto Ortiz de (2016)
The object of study of this thesis is the metaphoric concept “the costumer is king”, which aims to analyze the influence of the popular management, or the pop-management, on the social construction of the costumer. Sustained by this theoretical framework, this thesis assumes that the referred concept is current in the organization´s circulating speeches and the aspects related to the organizational practices and discourses need to be better understood in its limitations and contradictions. The researcher, therefore, identified as its data source the announced constructions in the HSM Management Magazine, due its editorial focus in producing exclusively contents to business management. The theoretical framework of this study is broadly influenced by the Business Administration perspective and Organization Discourse. The methodology of this research, first, comprehends data collection from public documents and, second, the analysis and the interpretation of the data based on the principles of Discourse Analysis approach, with the view in the everyday meaning production. The finding results allow inferring that the concept of “the costumer is king” is embedded in the speeches of HSM Management magazine, as it emerges sovereign costumer characteristics as: autonomy, rationality and power in the consumption relationships. However, to a lesser or greater extent, it is possible to observe that there are additional social representations that hang over the costumer and the consumer, which contradict the cited pillars that supports the image of the sovereign costumer